MEKANISME KEAMANAN MESIN LAS RESISTANSI MENGGUNAKAN SENSOR INFRA MERAH PASIF BERBASIS TEKNOLOGI MIKROKONTROLER - Nadjamudin; joni eka candra (JURNAL QUANCOM: QUANTUM COMPUTER JURNAL, 2023)
Arduino is an open-source based microcontroller derived by wiring platform that has its own programming language and is designed to facilitate the designer of electronic devices in various fields. The main component is a microcontroller chip with AVR type from Atmel company.In the world of intelligent system electronics are widely used microcontroller devices, both as controls, displays, sensor readings and data processing. Now, there is a type of microcontroller that is easy to use and quickly mastered the Arduino. There are various types of arduino in terms of size, function and the complexity of its function. By understanding the basic principles of microcontroller work in its application on arduino, the design of electronic equipment can be easily realized.